Referral Patterns for the Evaluation of Asymptomatic Microscopic Hematuria in Women in a Single Health Care System: Room for Improvement. Issue 2 (August 2019) - Handler, Stephanie J.; Ackerman, A. Lenore; Samimi, Parisa. A.; Bresee, Catherine; Anger, Jennifer T.; Eilber, Karyn S.
Abstract : OBJECTIVE: To identify patterns of care for women referred for asymptomatic microhematuria in a single, hospital-based health care system and estimate the cost of unindicated evaluation. METHODS: We conducted a retrospective study of 100 women with a diagnosis of asymptomatic microhematuria referred to a tertiary female pelvic medicine and reconstructive surgery practice. Our analysis focused on referral patterns by obstetrician–gynecologists and primary care physicians. Data analyzed included whether asymptomatic microhematuria was documented using urine microscopy (vs urine dipstick) and whether the urine microscopy correctly identified asymptomatic microhematuria with three red blood cells (RBCs). RESULTS: Forty-six patients were referred who met the American Urological Association's guidelines for asymptomatic microhematuria with a workup estimated at 8, 298 per patient. Fifty-four were referred to a female pelvic medicine and reconstructive surgery specialist despite clearly not meeting the American Urological Association's definition of asymptomatic microhematuria. Of these, 33 patients were referred based on dipstick-positive results only, 11 were referred based on microscopic urinalysis demonstrating fewer than three RBCs per high-power field (HPF), and the remaining 10 patients were referred with urine microscopy demonstrating at least 3 RBC/HPF but in the setting of a clearly benign cause, such as infection or menstruation. The total estimated cost of the unnecessary asymptomatic microhematuria workup in patients who did not meet American Urological Association criteria for referral was 1, 213 per patient. CONCLUSION: Fewer than half of the referrals for asymptomatic microhematuria were appropriate, leading to wasted and entirely preventable health care expenditures. This study highlights the need for education of health care providers making these referrals. Abstract : Most asymptomatic microhematuria referrals to female pelvic medicine and reconstructive surgery specialists in our health care system are not appropriate, and education of referring providers is needed.